Knowledge, attitude and practice of medical students towards COVID19 in Sudan: A cross sectional study among 19 universities. (December 2022) - Alfatih, Mohammed; Mohamed Ahmed, Khabab Abbasher Hussien; Alhusseini, Radi Tofaha; A. Hasabo, Elfatih; Hemmeda, Lina; Elnaiem, Walaa; Mohamed, Rua Isameldin Bakhiet; Abdalla, Monzer Omer Ahmed; Abdalmaqsud muhmmed, Khadija ala; Taha, Osama Mohammed Nowar; Husni Yousef, Yaman Shurki Adel; Hassan Alrufai, Rawan Raad; et al.
Abstract: Background: Since December 2019, an outbreak of severe respiratory infection (COVID-19) emerged in the city of Wuhan in China. The knowledge, awareness and practice of medical students toward COVID-19 pandemic is of most importance as it demonstrates their preparedness to deal with this pandemic. The objective of this study is to assess the knowledge, awareness and practice of medical students in Sudan universities about COVID 19. Methodogy: This is a cross-sectional study conducted on 19 universities that have medical schools in Sudan. Data from at least 100 medical students from each university were included in the study. Data were collected using an online questionnaire in April 2020. Statistical analysis was conducted using the Statistical Package for Social Science software, version 25. Results: About 2603 medical students from 19 universities were included. Overall good knowledge and practice were demonstrated by the medical students (88.9%) and (78.6%), respectively. Respondents who answered that the most common clinical symptoms of COVID-19 were the main combination of dry cough, fatigue and fever were (27.7%), and the first initial symptom was headache were (48.3%.). (60.2%) Wear medical masks, (95%) said that avoiding crowded places protects against the spread of COVID-19, and (50.7%) have confidence that Sudan can win the battle against the COVID-19. Finally, (68.8%) agreed that COVID-19 will finally be successfully controlled. Conclusion: This study has found that medical students in Sudan demonstrated good knowledge and good practice toward Covid19. Highlights: Covid-19 pandemic has captured the attention of the world due to severe political, social, psychological, and economic influences. This study has found that medical students in Sudan demonstrated good knowledge and good practice toward COVID-19.